How Self Awareness Bridges Growth Mindset, Innovative Leadership, Work Engagement Toward Innovative Work Behavior - Riyoko, Sisno; Egga Septiani Wulandari; Widiastuti, Anna (Jurnal Manajemen, 2026)
This study aimed to analyse the mediating role of self-awareness in the relationship between growth mindset, innovative leadership, and work engagement on innovative work behaviour among teachers and staff. The focus of the study was on how self-awareness could be a psychological mechanism that bridged these antecedent factors so that they were truly manifested in innovative work behaviour. The approach used was explanatory quantitative with primary data sources involving a population of teachers and staff at Madrasah Terpadu Kabupaten Jepara. Of the total population, 144 respondents participated by completing a structured questionnaire, so that the data obtained reflected the actual conditions in that environment. The results of the study indicated that growth mindset and work engagement had a significant influence on Innovative Work Behaviour, while innovative leadership did not have a direct influence. However, self-awareness had been proven to play an important mediating role in the overall relationship. These findings confirmed that self-awareness was a psychological bridge that could transform a growth mindset, innovative leadership, and work engagement into actual innovative work behaviour. This study contributed theoretically by expanding the understanding of mediation mechanisms in innovative work behaviour, particularly by positioning self-awareness as a psychological bridge connecting growth mindset, innovative leadership, and work engagement with innovative work behaviour. This study also provided scientific contributions by strengthening the integration between the Job Demands–Resources Model and Social Cognitive Theory, as well as introducing self-awareness as a mediation mechanism that had not been widely studied in the context of education.